Determinación de niveles de mercurio de orina a los mineros artesanales del sitio El Pache del cantón Portovelo. - Bonilla Rivera, Jorge G. (2010)
This report gathers the results of quentitative evaluation of mercury levels in samples of urine 24 hours in worker artisanal miners the Portovelo canton Pache site located in the upper part of the province of gold.